2016
DOI: 10.4081/pmc.2016.134
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal gastrointestinal involvement and congenital cytomegalovirus

Abstract: Cytomegalovirus (CMV) is the most common cause of congenital viral infection, affecting 0.2 to 2.3% of all live births in developed countries. Very low birth weight and extremely low birth weight newborns are at higher risk of symptomatic CMV infection, most commonly secondary and acquired through breast milk. Gastrointestinal involvement is rare in acquired CMV infections, but it could be an important manifestation of postnatal infection in preterm infants admitted to neonatal intensive care units. Early onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Bonnard et al also reported that CMV may cause intestinal atresia and perforation when combined with other local factors such as ischemia (12). CMV infection in the gastrointestinal tract is associated with vasculitis of an affected segment and cause perforation in the immunocompromised host or premature or low birth weight infants (13). Thus, although the incidence or the causality of CMV for gastrointestinal involvement in premature infants are not demonstrated to date, there are accumulating findings which support a hypothesis that CMV has an important role in such gastrointestinal disease at least by exacerbating the course of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonnard et al also reported that CMV may cause intestinal atresia and perforation when combined with other local factors such as ischemia (12). CMV infection in the gastrointestinal tract is associated with vasculitis of an affected segment and cause perforation in the immunocompromised host or premature or low birth weight infants (13). Thus, although the incidence or the causality of CMV for gastrointestinal involvement in premature infants are not demonstrated to date, there are accumulating findings which support a hypothesis that CMV has an important role in such gastrointestinal disease at least by exacerbating the course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among the causative etiology of severe gastrointestinal complication in premature infants (e.g., prematurity, ischemia, indomethacin for PDA), CMV infection is regarded as rare ( 13 ) and generally not included in the differential diagnosis of gastrointestinal disease in premature newborns, however recent study showed that CMV infection was highly prevalent in surgical intestinal specimen from infants with NEC or SIP and may exacerbate the course of NEC ( 11 , 15 ). Since definitive diagnosis of CMV infection in the intestine requires obtaining bowel tissue, there may be underdiagnosis of CMV-associated gastrointestinal disease in premature infants ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the existence of CMV in the stricture lesions was not confirmed, CMV was detected by immunohistochemistry in biopsy specimens from the jejunal ulcer and both symptoms and endoscopic findings improved after ganciclovir treatment, strongly suggesting that the multiple thin strictures of the jejunum were induced by CMV infection. There are a few reports of colonic and ileal strictures like DD that occurred secondary to CMV infection in infants 6 and adults 7 . To our knowledge, this is the first report of jejunal DD related to CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Cytomegalovirus (CMV) is the commonest intrauterine viral infection with less than forty reported cases of gastrointestinal involvement in the postnatal period [1,2].…”
mentioning
confidence: 99%
“…Perinatal CMV transmission is transplacental or postnatal [1]. Infected infants are rarely symptomatic at birth and gastrointestinal involvement is anecdotal in the immunocompetent [3].…”
mentioning
confidence: 99%